(untitled) (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
The housekeeping department is an essential part of the hotel industry, as is the hospitality management curriculum. Different trainings and seminars were also conducted to enhance the knowledge and skills of the students. Thus, this study aims to determine the efficacy of housekeeping simulations on the performance of BSHM students at Bestlink College of the Philippines. The study revealed that having a housekeeping simulation is strongly effective in those BSHM students’ performance; the impact of housekeeping practices may boost the students’ skills. However, some of the respondents encountered different challenges while performing housekeeping simulation. Based on the findings and data gathered, the researchers construct guidelines to improve the performance of BSHM students towards housekeeping simulations.